Type of Birth, Depression and Anxiety as Determinates of Breastfeeding Attitude among Nursing Mothers - Imhonde H. O.; Shaibu H; Imhonde J. E.; Lina Handayani (Intelektual Pustaka Media Utama, 2012)
This study examined Type of Birth, Depression and Anxiety as determinates of Breastfeeding attitude among Nursing Mothers in Edo and Kogi State Nigeria. A total of two hundred (200) currently Breastfeeding mothers participated in the study. This comprises of a hundred and twenty breastfeeding mother drawn from the General Hospital Auchi Edo State and eighty drawn from Ajaokuta Steel Medical Centre Kogi State. A questionnaire was used in collecting data. The questionnaire consisted of four sections. The demographic variables, Breastfeeding attitude scale, Depression and Anxiety sub-scales. Results of the study revealed that mothers who had normal delivery reported positive attitude towards breastfeeding than mothers who gave birth through caesarian section (t=3.38, df 198 P < 0.05). There were no significant differences in the reported attitude of mothers scoring high and low on the Zung depression inventory towards breastfeeding. Likewise there were no significant differences in the reported attitude of mothers scoring high or low towards breastfeeding. Results obtained also shows that there was an interaction effect between type of delivery and depression on breastfeeding attitude among nursing mothers. An interaction existed also between type of Delivery and anxiety; Depression and anxiety but surprisingly, type of delivery, depression and anxiety did not have an interaction effect on the prediction of breastfeeding attitude among nursing mothers. Based on the findings of this study, it was recommended that there is need for counseling and enlightenment campaign embarked upon by government, and non-governmental organization as well as all health professional concerned within Nigeria to eliminate this wrong attitude and belief about Caesarean section birth as well as campaign on the nutritional values of breastfeeding milk to children. The need for mothers who went through CS to be counseled on the need to believe in themselves as well as the benefit of breastfeeding to the child and mother is very important.DOI: http://dx.doi.org/10.11591/ijphs.v1i2.1253